2020
DOI: 10.1186/s13643-020-01524-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with antiretroviral treatment failure among people living with HIV on antiretroviral therapy in resource-poor settings: a systematic review and metaanalysis

Abstract: Background Despite the increase in the number of people accessing antiretroviral therapy (ART), there is limited data regarding treatment failure and its related factors among HIV-positive individuals enrolled in HIV care in resource-poor settings. This review aimed to identify factors associated with antiretroviral treatment failure among individuals living with HIV on ART in resource-poor settings. Methods We conducted a comprehensive search on M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 45 publications
3
29
0
1
Order By: Relevance
“…Adherence to ART also reduces rates of mother-to-child transmission (MTCT) of HIV (8)(9)(10)(11). Suboptimal adherence to ART is detrimental: it is associated with virologic failure (12)(13)(14)(15)(16)(17)(18)(19), drug resistance (12,(20)(21)(22)(23), and ultimately death (24)(25)(26)(27)(28)(29)(30). In 2014, the United Nations Program on HIV/AIDS (UNAIDS) launched the 90-90-90 global targets for HIV and AIDS programming.…”
Section: Introductionmentioning
confidence: 99%
“…Adherence to ART also reduces rates of mother-to-child transmission (MTCT) of HIV (8)(9)(10)(11). Suboptimal adherence to ART is detrimental: it is associated with virologic failure (12)(13)(14)(15)(16)(17)(18)(19), drug resistance (12,(20)(21)(22)(23), and ultimately death (24)(25)(26)(27)(28)(29)(30). In 2014, the United Nations Program on HIV/AIDS (UNAIDS) launched the 90-90-90 global targets for HIV and AIDS programming.…”
Section: Introductionmentioning
confidence: 99%
“… 30 A study conducted in a developing nation found that patients with CD4 counts below 200 cells/mm 3 had nearly five times higher chance of treatment failure than those with CD4 counts above 200 cells/mm 3 . 31 Viral replication reduces when CD4 cell count rises, implying that viral burden is inversely proportional to CD4 cell count. When compared with immune-competent patients with HIV infection, patients with deteriorated immune status had raised viral load.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, it was found that persons were more likely to be virally suppressed at 12 months if they had baseline CD4 counts ≤ 200 cells/mm 3 (OR, 1.71; 95% CI 1.26–2.32) however the results were not statistically significant for retention in care at 12 months. There are mixed results in patients with CD4 < 200 cells/mm 3 and subsequent viral suppression as a systematic review by Lailulo et al [ 29 ] done to identify factors associated with ART treatment failure showed that the likelihood of treatment failure was significantly higher in patients with CD4 < 200 cells/mm 3 (OR, 4.82; 95% CI 2.44–9.52) in resource limited areas perhaps due to HIV related opportunistic infections, increased pill burdens and the potential to develop increased drug toxicity in patients with advanced disease on multiple medications [ 29 ].…”
Section: Discussionmentioning
confidence: 99%